Hydrocarbon sources for the carbon nanotubes production by chemical vapour deposition: a review - Abdullah, Hayder Baqer; Ramli, Irmawati; Ismail, Ismayadi; Yusof, Nor Azah (Universiti Putra Malaysia Press, 2017)
The synthesis of carbon nanotubes (CNTs) using a chemical vapour deposition (CVD) method requires the use of hydrocarbon as the carbon precursor. Among the commonly used hydrocarbons are methane and acetylene, which are both light gas-phase substances. Besides that, other carbon-rich sources, such as carbon monoxide and coal, have also been reportedly used. Nowadays, researches have also been conducted into utilising heavier hydrocarbons and petrochemical products for the production of CNTs, such as kerosene and diesel oil. Therefore, this article reviews the different kind of hydrocarbon sources for CNTs production using a CVD method. The method is used for it allows the decomposition of the carbon-rich source with the aid of a catalyst at a temperature in the range 600-1200°C. This synthesis technique gives an advantage as a high yield and high-quality CNTs can be produced at a relatively low cost process. As compared to other processes for CNTs production such as arc discharge and laser ablation, they may produce high quality CNTs but has a disadvantage for use as large scale synthesis routes.